Penetração de cloretos em concretos compostos com cinza de casca de arroz de diferentes teores de carbono grafítico - Zamberlan, Fabricio Beltrame (2013)
In addition to compressive strength, durability is an important variable to be taken into account in the mix design of concrete. Concrete must be able to withstand the action of aggressive agents and function as a protective layer that can block the penetration of corrosive substances that could affect the reinforced steel frame. The use of mineral additions in concrete has been shown to improve a range of physical properties in concrete while providing an environmentally sound alternative in the use of industrial by-products that would otherwise make their way into landfill sites. This study aimed to assess the penetration of chloride ions in concrete samples with the addition of white and dark rice husk ash and different concentrations of graphitic carbon and different curing periods. The concrete samples were prepared with content of 5%, 10%, 20% and 30% of mineral additions as substitution for high early strength Portland cement (CPV – ARI). Different water/binder ratios (0.35; 0.50; 0.65) were used and the samples were cured in a wet chamber for 3 and 7 days. Two samples with 5% and 10% silica fume as substitution for Portland cement were used as control mixes. Chloride penetration by immersion in a saline solution was determined in test specimens measuring 100mm x 100mm x 285mm at the ages of 7, 14, 28, 56 and 91 days. A Rapid Chloride Penetration Test was carried out as defined in ASTM C1202/05 in test specimens measuring 100mm x 51mm tested at 28 and 91 days. Results showed a better performance of white rice husk ash when compared to dark rice husk considering chloride penetration. The increase in the content of rice husk ash reduced the total Coulomb charge (Q), which was more significant at levels up to 20% substitution. The use of two types of rice husk ash as well as silica fume in substitution for cement showed a better performance regarding penetration of chloride ions for all levels of replacement, water/binder ratios,and curing periods tested when compared to the reference mixture. Thus, one may conclude that the use of mineral addition on properties of concrete durability is efficient.